Anterior loop of the mental nerve in Saudi sample in Riyadh, KSA. A cone beam computerized tomography study - Osama Saeed Alyami; Mazen Saeed Alotaibi; Pradeep Koppolu; Abdulrahman Alosaimy; Ashraf Abdulghani; Lingam Amara Swapna; Dalal H Alotaibi; Ali Alqerban; Kizhakke Veetil Sheethi (Elsevier, 2021)
Background: The portion of inferior alveolar nerve (IAN) existent anterior to the mental foramen, before parting the canal, is referred to as the anterior loop (AL) of the IAN. The presence of AL is important when placing the implant interforaminal area of the mandible. These anatomical discrepancies can be assessed by cone-beam CT (CBCT), for evaluating its position and exact location. The AL is classified into Types I, II and III. In Type I, Y-shaped anatomy; in Type II, anatomy is T-shaped; and in Type III, Y-shaped anatomy is seen, and the incisive branch is thicker as compared to the main branch. Aim: In this study, we aim to analyse the prevalence of different types of AL of the IAN in Saudi sample population. Materials and Methods: The present study is a retrospective analysis of 149 (86 female & 63 male) CBCT images of patients records from 2018 June to 2018 September in the department of implant dentistry, KSMC, Riyadh. The age range of the patients who participated in the study was 30-60 years. The mean age of female participants is 42.5 ± 5.8, for the male participants is 48.6 ± 11.4 years respectively. Results: The most frequent type of AL of mental nerve noticed on the right side was of type I (59.1%), followed by type II (27.5%) and type III (13.4%). The most frequent type of AL of mental nerve noticed on the left side was type I (61.7%), followed by type II (26.8%) and type III (11.4%). Conclusion: The results of the study encourage the usage of CBCT for planning implant treatment. We also suggest that it is obligatory for professionals to categorise the presence of AL and to measure them appropriately when planning for the procedures in the interforaminal region.